Impact of Additional Transthoracic Electrical Cardioversion on Cardiac Function and Atrial Fibrillation Recurrence in Patients with Persistent Atrial Fibrillation Who Underwent Radiofrequency Catheter Ablation - Deguo Wang; Fengxiang Zhang; Ancai Wang (Cardiology Research and Practice)
Backgrounds and Objective. During the procession of radiofrequency catheter ablation (RFCA) in persistent atrial fibrillation (AF), transthoracic electrical cardioversion (ECV) is required to terminate AF. The purpose of this study was to determine the impact of additional ECV on cardiac function and recurrence of AF. Methods and Results. Persistent AF patients received extensive encircling pulmonary vein isolation (PVI) and additional line ablation. Patients were divided into two groups based on whether they need transthoracic electrical cardioversion to terminate AF: electrical cardioversion (ECV group) and nonelectrical cardioversion (NECV group). Among 111 subjects, 35 patients were returned to sinus rhythm after ablation by ECV (ECV group) and 76 patients had AF termination after the ablation processions (NECV group). During the 12-month follow-ups, the recurrence ratio of patients was comparable in ECV group (15/35) and NECV group (34/76) (44.14% versus 44.74%, P=0.853). Although left atrial diameters (LAD) decreased significantly in both groups, there were no significant differences in LAD and left ventricular cardiac function between ECV group and NECV group. Conclusions. This study revealed that ECV has no significant impact on the maintenance of SR and the recovery of cardiac function. Therefore, ECV could be applied safely to recover SR during the procedure of catheter ablation of persistent atrial fibrillation.